Medial epicondyle avulsion after elbow dislocation in an adolescent non-professional soccer player treated with a cannulated screw: a case report - Pedrazzini, Alessio; Visigalli, Alberto; Valenti, Piergiulio; Bertoni, Nicola; Yewo Simo, Henry; Bisaschi, Roberto; Medina, Vanni; Pedrabissi, Bianca; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Medial epicondyle fractures of the humerus account for 11–20% of all elbow injuries in children and in 30–55% of cases they are associated with an elbow dislocation. Undisplaced fractures are usually treated conservatively but literature is controversial regarding the treatment of displaced fractures (≥5mm) in paediatric fractures. In recent years, there is an emerging consensus that such patients may benefit more from open reduction and internal fixation. Authors report a case of a 15 years old nonprofessional soccer player who suffered of an elbow dislocation with an intra-articular fragment derived from avulsion of the medial epicondyle. Methods: Clinical and instrumental evaluation confirmed elbow dislocation with an intra-articular fragment derived of the medial epicondyle. After the reduction an open reduction and internal fixation with cannulated screw was performed. Results: Clinical evaluation after 90 days showed resolution of pain and almost complete ROM and complete recovery of strength and of functionality of the operated limb. Furthermore, x-rays demonstrated consolidation of the fracture. Conclusions: this case confirms that a precise evaluation of the fracture and its displacement is at the base of satisfactory outcomes. If fracture is displaced≥5mm and patient is near skeletal maturity open reduction and fixation is indicated.